2006
DOI: 10.1099/mic.0.28490-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-mediated genomic recombination at the pilin gene locus enhances the N-acetyl-d-galactosamine-specific haemagglutination activity and the growth rate of Eikenella corrodens

Abstract: Eikenella corrodens belongs to a group of periodontopathogenic bacteria and forms unique corroding colonies on solid medium due to twitching motility. It is believed that an N-acetyl-d-galactosamine (GalNAc)-specific lectin on the cell surface contributes significantly to its pathogenicity and can be estimated by its haemagglutination (HA) activity. Recently, a plasmid, pMU1, from strain 1073 has been found; this plasmid affects pilus formation and colony morphology. To identify the gene involved in these phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…We suggested earlier that the GalNAc-specific lectin and other factors contributed additively to biofilm formation in some strains of E. corrodens [11]. In this study, we demonstrate that the introduction of ORF4 enhanced both GalNAc-specific lectin activity and biofilm formation.…”
Section: Effect Of Orf4 On Biofilm Formationsupporting
confidence: 55%
See 4 more Smart Citations
“…We suggested earlier that the GalNAc-specific lectin and other factors contributed additively to biofilm formation in some strains of E. corrodens [11]. In this study, we demonstrate that the introduction of ORF4 enhanced both GalNAc-specific lectin activity and biofilm formation.…”
Section: Effect Of Orf4 On Biofilm Formationsupporting
confidence: 55%
“…Previously, we reported that introduction of ORF4 into strain 23834 resulted in increased biofilm formation [11]. Here, we investigated whether the same occurred in other E. corrodens strains.…”
Section: Effect Of Orf4 On Biofilm Formationmentioning
confidence: 99%
See 3 more Smart Citations